Perinatal psychological distress in the South African context: The road to task shifting evidence based interventions - Spedding, Maxine F (Department of Psychiatry and Mental Health, 2017)
Inadequate public health resources coupled with a chronically overburdened health system leave a large proportion of South Africans unable to access mental health care. Low-income pregnant women with common mental disorders (CMDs) are arguably more vulnerable to falling through the treatment gap, given the low rates of detection during pregnancy and the numerous additional barriers to care. The direct and indirect financial and personal costs associated with perinatal mental illness are substantial, while the high prevalence rates of perinatal CMDs make this an area in need of urgent attention. Integrating task shifting approaches into perinatal primary health care services is a promising solution. The first chapter introduces the thesis, providing context to the studies that are presented in later chapters and an overview of the research questions that informed them. The second chapter constitutes a systematic review of the literature relevant to the studies. Chapters 3 to 6 report on the findings of the studies, briefly described in the abstract below. The prevalence and risk factors associated with perinatal psychological distress - a plausible precursor for common mental disorders (CMDs) - are not widely understood in under-resourced settings. The first study (Chapter 3) investigates the prevalence and predictors of psychological distress in the antenatal period. Data were collected from 664 pregnant women who reported for antenatal care to any one of 11 Midwife and Obstetric Units (MOU) across the greater Cape Town area. Psychological distress was measured using the Symptom Response Questionnaire (SRQ-20; cut-off value of 7/8), while data pertaining to risk factors were collected via a demographic questionnaire, the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) and the Multidimensional Scale of Perceived Social Support (MSPSS). The prevalence of antenatal psychological distress was 38.6%. Risk factors included low socio-economic status (SES) (OR = 1.45, 95% CI: 1.24-1.68); recent physical abuse and/or rape (OR = 1.94, 95% CI: 1.57-2.40); complications during a previous delivery (OR = 1.18, 95% CI: 1.01-1.38); having given birth before (OR = 1.61, 95% CI: 1.21-2.14). The high prevalence rate of psychological distress is consistent with those found in other South African studies of perinatal CMDs. Appropriate, context-specific, and effective interventions are better served by investigating a broader range of symptoms associated with perinatal CMDs in these settings. The second study (Chapter 4) examines the mental health literacy (MHL) of pregnant women, including their perceptions of the causes of mental illness during pregnancy and best treatment approaches. Understanding the factors that represent barriers to accessing care is important to the development of accessible interventions. Globally, low levels of mental health literacy have often been identified as one such treatment barrier. However, little is known about how pregnant women perceive and understand mental illness during this time, particularly in South Africa. A convenience sample of 262 pregnant women attending routine antenatal appointments at a Midwife and Obstetrics Unit (MOU) were recruited to participate in the study. Participants were presented with one of five possible vignettes, depicting a woman with perinatal mental illness, as defined by the DSM 5, including ante- and postnatal depression, panic disorder, substance dependence and schizophrenia. Participants were then asked to provide a diagnosis and completed two scales assessing aspects of mental health literacy. The results from this study showed that more than three quarters of respondents (77.4%) did not identify the signs and symptoms described in the vignettes as those consistent with mental illness. More than half of all participants (57.5%) were of the view that all the disorders depicted were "typical of a weak character", while stress was the most widely held explanation for symptoms of all disorders. Participants were most confident in the therapeutic potential of psychological services, especially consulting with a counsellor or social worker. These were closely followed by lifestyle and self-help options as the most endorsed means to addressing psychiatric symptoms during pregnancy. Notably, seeking help from a spiritual or religious advisor was comparably as popular among participants as seeking help from a psychologist or social worker. Given the elevated prevalence of perinatal mental illness, these findings are cause for concern. Developing socio-culturally nuanced understandings of how perinatal mental illness is perceived should be emphasized as central to the development of successful interventions. The third study (Chapters 5 and 6) investigates the feasibility and acceptability of, as well as the preliminary responses to an adapted Problem Solving Therapy (PST) intervention to treat psychological distress. Given the large treatment gap that exists in public mental health, support for task shifting evidence based mental health treatments is growing. However, the gaps in our knowledge are threefold. First, most research has used lay counsellors to deliver interventions. No research has used Registered Counsellors (RC) to conduct interventions. Second, very little is known about the potential outcomes of task shifting an adapted PST intervention to reduce symptoms of psychological distress. Third, data regarding the feasibility and acceptability of such interventions in South African Midwife and Obstetric Units (MOUs) is very limited. Results from the study are presented in two chapters. Chapter 5 focuses on the intervention participants. Thirty-eight women who screened positive for high CMD symptoms on the Edinburgh Postnatal Depression Scale (EPDS) at their first antenatal visit were recruited to participate in the intervention. Of these, 22 completed the preand post-intervention interviews. Using mixed methods, preliminary responses to the threesession PST intervention, as well as participants' perceptions of the intervention's feasibility and acceptability were explored. Primary outcomes included psychological distress as measured by the Symptom Response Questionnaire (SRQ-20) and CMD symptoms, as measured by the EPDS. A short semi-structured post-intervention interview was also conducted approximately three months after each participant's last session. On the primary outcome measures, significant reductions were seen on EPDS scores (z = -3.0, p < 0.01) as well as the SRQ-20 scores (z = -3.5, p = <0.01). Several significant reductions were also seen on secondary outcomes. Reductions in impairment to functioning were also noted, with all three Sheehan disability scales reflecting less disruption to work (z = -2.3, p = 0.02), social life (z = -3.3, p < 0.01), as well as family and home responsibilities (z = -2.5, p = 0.01). Perceived Stress Scale scores were also significantly reduced (z = -3.4, p < 0.01). Significant changes were seen on two problem-solving styles, with reduced 'negative problem orientation' scores (z = -3.1, p < 0.01) and 'avoidant style' scores (z = -3.0, p < 0.01) Participants felt that the intervention was feasible and acceptable. The intervention's acceptability lay primarily in the opportunity for participants to talk confidentially to a non-judgmental and empathic person about their problems. The intervention materials seemed to serve as an extension of the therapeutic process. Factors that were identified by participants as representing potential barriers to the intervention included lack of transport or money, work commitments and stigma. Chapter 6 explores the intervention's feasibility and acceptability from the perspectives of 6 stakeholders who were involved with the project. Semi-structured interviews were conducted with each stakeholder. Data from the interviews showed that the stakeholders felt that the intervention was helpful to patients and a valuable resource for the facility to have. Some expressed concern about how stigma associated with mental illness might be a barrier to patients who need mental health care. To the staff, the project's value seemed to lie primarily in the support it provided in managing emotionally distressed patients. Having a resource to refer patients to appeared to provide overburdened staff with some relief. None of the stakeholders reported that the screening and referral procedures added to their workload. Some stakeholders felt detection of psychological problems among patients was compromised without mental health screening. Staff felt that a walk-in counselling service would serve to improve future interventions. Limitations to the first study included its cross-sectional design and use of a screening tool to measure the prevalence of psychological distress. The second study was limited by the employment of vignettes to collect data. While they are useful tools to elicit population-specific responses, their adaption for those purposes means that they are not standardised. The study was further limited by the use of a convenience sample. Finally, the third study was limited by a small sample size owing to low retention rates. However, low retention rates are not uncommon among antenatal and low-income populations, where structural barriers to accessing care are often more pronounced. The lack of a comparison group was an additional limitation. In conclusion, data from this study support task shifting evidence based treatments to Registered Counsellors to treat the highly prevalent antenatal psychological distress. Difficulties distinguishing CMD symptoms from normal pregnancy experiences may influence the uptake of counselling services and represent a barrier to care. Improving mental health literacy may be a necessary supplement to future interventions. Future research should focus on evaluating real-world models of integrated mental health in primary care settings. How psycho-education programmes might impact upon the uptake of services at antenatal care facilities will also contribute to broadening our knowledge of developing effective and appropriate interventions.